ANALISIS HUKUM TERHADAP KEPEMILIKAN TANAH PERTANIAN YANG MELEBIHI BATAS MAKSIMUM BERDASARKAN UNDANG-UNDANG NOMOR 56 PRP TAHUN 1960 STUDI DI KABUPATEN BENGKALIS PROVINSI RIAU - RIZKI NAINGGOLAN (PREMISE LAW JURNAL, 2018)
Dosen Pembimbing:1. Prof. Dr. Muhd Yamin SH, MS, CN2. Prof. Dr. Syafruddin Kalo, SH, MHum3. Abdul Rahim Lubis, SH, MKnLand as God’s blessing for the Indonesian people has social function and its use should be able to increase people’s welfare. The right of management is mostly used by the government or legal entities to carry out their tasks and social affairs in economic field; but, since it is not its scope, it needs cooperation with the third party because the land of the Right of Management can be given to the third party for regional development so that the right of ownership, The research used descriptive analytic with juridical empirical method which analyzed, explained, and described the implementation of the burden of hypothecation on the right of management. The research used legal and conceptual approach in order to find out the legality and obstacles in burdening hypothecation on building rights on the right of management. Building rights on the right of management can be used as the collateral for debt by doing the burden of hypothecation on building rights as it is regulated in Article 4, paragraph 1 of Law No. 4/1996 on Hypothecation on land and everything which is related to it.. The holder of building rights files a request for the extension to the Land Office, and he has to fulfill the requirements for the extension of building rights in order to obtain permit as the holder of the right of management in the burden of hypothecation in building rights on the right of management.Keywords: Hypothecation, Building Rights, Right of Management